PENERAPAN METODE PRAKTIKUM DALAM PEMBELAJARAN KIMIA UNTUK MENINGKATKAN MINAT BELAJAR BAGI SISWA SMA PGRI JAYAPURA - Lodwyk N. Krimadi; Diana M. Abulais; Himawan Himawan; Juniati A. Bokin (LPPM Uncen, 2022)
The practicum method is one method that can be used in learning chemistry to improve mastery of scientific concepts and develop problem solving skills. This service is carried out at SMA PGRI Jayapura, Papua Province. The purpose of this service is to increase interest in learning chemistry, and to grow and train students' creativity in chemistry through simple practicums. The topics for this service are NaOH and HCl titration, electrochemistry, making metal batteries, and simple calorimeters using stayroform. The achievements of this community service activities have a positive impact on students. The students were very enthusiastic, active, and interactive. The students become motivated and eager to learn chemistry.Keywords: training; Practicum methods; Chemistry learning; SMA PGRI Jayapura